Nilai-Nilai Etika Bisnis Islam Sebagai Pondasi Pengembangan PT. Bank Syariah Indonesia (Perspektif Hukum Islam dan Global Compact) - El Muna, Naily (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Abstract: This study portrays the efforts of Islamic banking to motivate employees in familiarizing the values ​​of Islamic business ethics. The development of Islamic banking has experienced significant growth. A survey by the financial services authority (OJK) stated that the assets of the Islamic banking industry increased 14 times from Rp. 21.5 trillion in 2005 to Rp. 296, 2 trillion in 2015. Islamic Banking I should implement the values ​​of Islamic Business Ethics (EBI) in accordance with Islamic law. These values ​​are divine values, balance (justice), freedom and responsibility. Researchers used a qualitative approach to normative juridical case studies. The findings and theories were built using snowball sampling, which is the process of searching for data from and according to needs. Data collection was carried out by: interviews, observation, and documentation. Data analysis used: data reduction, data presentation, drawing conclusions. The results of this study include: (1) EBI habituation process: (a) As a spirit, (b) There is an emotional bond, the equality of managers, and users of customer funds, (c) The principle of the object is halal, mutual acceptance, needs, habits, and existential, (d) Being accounted for in a balanced manner in the form of scope of work, (2) The process of familiarizing EBI with employees in accordance with Islamic law.